Restructuring brain drain: strengthening governance and financing for health worker migration - Tim K. Mackey; Bryan A. Liang (Taylor & Francis Group, 2013)
Background: Health worker migration from resource-poor countries to developed countries, also known as ‘‘brain drain’’, represents a serious global health crisis and a significant barrier to achieving global health equity. Resource-poor countries are unable to recruit and retain health workers for domestic health systems, resulting in inadequate health infrastructure and millions of dollars in healthcare investment losses. Methods: Using acceptable methods of policy analysis, we first assess current strategies aimed at alleviating brain drain and then propose our own global health policy based solution to address current policy limitations. Results: Although governments and private organizations have tried to address this policy challenge, brain drain continues to destabilise public health systems and their populations globally. Most importantly, lack of adequate financing and binding governance solutions continue to fail to prevent health worker brain drain. Conclusions: In response to these challenges, the establishment of a Global Health Resource Fund in conjunction with an international framework for health worker migration could create global governance for stable funding mechanisms encourage equitable migration pathways, and provide data collection that is desperately needed.